2002
DOI: 10.1108/03074350210767988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the productive efficiency and performance of US commercial banks

Abstract: Reviews previous research on the efficiency and performance of financial institutions and uses Siems and Barr’s (1998) data envelopment analysis (DEA) model to evaluate the relative productive efficiency of US commercial banks 1984‐1998. Explains the methodology, discusses the input and output measures used and relates bank performance measures to efficiency. Describes the CAMELS rating system used by bank examiners and regulators; and finds that banks with high efficiency scores also have strong CAMELS rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 22 publications
8
53
0
14
Order By: Relevance
“…The finding is consistent with earlier findings by among others, Kwan and Eisenbeis (1995), Resti (1997) and Barr et al (2002) have found a negative relationship between problem loans and banks efficiency. Furthermore, most research conducted on explaining the causes of bank or thrift industry failures have found that failing institutions carried a large proportion of non-performing loans in their books prior to failure (Dermiguc-Kunt, 1989;Whalen, 1991;Barr and Siems, 1994).…”
Section: The Determinants Of Malaysian Islamic Banks Efficiencysupporting
confidence: 83%
“…The finding is consistent with earlier findings by among others, Kwan and Eisenbeis (1995), Resti (1997) and Barr et al (2002) have found a negative relationship between problem loans and banks efficiency. Furthermore, most research conducted on explaining the causes of bank or thrift industry failures have found that failing institutions carried a large proportion of non-performing loans in their books prior to failure (Dermiguc-Kunt, 1989;Whalen, 1991;Barr and Siems, 1994).…”
Section: The Determinants Of Malaysian Islamic Banks Efficiencysupporting
confidence: 83%
“…Many studies have used CAMELS rating system to analyze the performance of financial institutions and found the system quite useful in terms of judging their financial conditions. For example, Barr et al (2002) argued that "CAMEL rating has become a necessary evaluating instrument for regulators".…”
Section: Literaturementioning
confidence: 99%
“…A study conducted by Barr et al (2010) viewed that CAMEL rating criteria has become a concise and indispensable tool for examiner's and regulators. This rating criteria ensures a bank's healthy conditions by reviewing different aspects of a bank based on variety of information sources such as financial statement, funding sources, macroeconomics data, budget and cash flow.…”
Section: Literature Reviewmentioning
confidence: 99%